Cerebral Amyloid Angiopathy presenting as Cognitive Decline - Balagopal, Krishnan; Nadarajah, Jeyaseelan; Jaisukhalal, Jaisurya; Iqubal, Mishal Raees; Ajith, Karthika (Nepal Journal of Neuroscience, 2023)
Cerebral amyloid angiopathy (CAA) is a disorder seen as age advances, characterized by the accumulation of amyloid within the leptomeninges and cerebral blood vessels. Lobar hemorrhages are the most common clinical manifestation seen. Cognitive decline due to repeated cerebral microhemorrhages in one of the rare presentations seen mainly in the elderly. We present here a case of a seventy year old female patient who presented with a one year history of progressive cognitive impairment. She was detected to have CAA on imaging with both cortical microbleeds and extensive superficial siderosis. She was started on cholinesterase inhibitors and antipsychotics for her symptoms. Antiplatelet agents were avoided due to increased risk of hemorrhage. This report highlights the importance of CAA as a cause of cognitive decline in elderly patients and also its therapeutic implications